Analiza ekonomiczna (kosztów i korzyści) przedsięwzięć inwestycyjnych - Baron, Magdalena (Economic Analysis (Cost-Benefit Analysis) of Investment Projects, 2006)
The article presents theoretical basis of cost-benefit analysis of investment projects. The concept of efficiency in the aspect of rational allocation of resources, the Pareto and Kaldor-Hicks criterion, the concept of costs and benefits as alternative cost and willingness to pay respectively and the indicators employed in economic analysis of investment projects are presented. The article indicates also the wide range of applicability of the analysis in the process of decision-making in many countries and international organisations, especially in the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 34-44